The last stop in Yuma County [videorecording (Blu-Ray)] - Compton, Matthew (Well Go USA Entertainment, 2024)
While waiting for the next fuel truck at a rural Arizona rest stop, a traveling knife salesman delivers a half-hearted sales pitch to the owner of the diner. As two suspicious men arrive, their distinctive car is recognized as one seen fleeing a bank heist. Willing to protect their bloodstained money and ready to eliminate witnesses, the Mexico-bound robbers are forced to make an uneasy truce in this dire hostage situation when others arrive. As tension builds, the knife salesman makes a fateful decision that will change his life forever.